Comparative Outcomes of Mechanical Thrombectomy and Catheter-Directed Thrombolysis in Acute Lower Limb Ischemia: A Systematic Review and Meta-Analysis - Ida Bagus Ardya Kurnia Wilananda; I Nyoman Semadi (Bali Medical and Wellness Journal, 2026)
Background: Acute lower limb ischemia (ALI) is a time-sensitive vascular emergency associated with substantial risk of limb loss and mortality. Although catheter-directed thrombolysis remains a commonly utilized endovascular therapy, thrombectomy-based approaches have increasingly been adopted because they allow more rapid thrombus removal with potentially lower thrombolytic exposure. This study aimed to compare the clinical outcomes of mechanical thrombectomy (MT) and catheter-directed thrombolysis (CDT) in patients with acute lower limb ischemia. Methods: A systematic review of comparative studies evaluating mechanical thrombectomy and catheter-directed thrombolysis for acute lower limb ischemia was performed using multiple electronic databases. Mortality and major complications were analyzed as primary endpoints, while minor complications and hospital length of stay were assessed as secondary outcomes. Pooled analyses were generated using random-effects models. Results: Six comparative studies met the eligibility criteria. Mortality outcomes were comparable between thrombectomy- and thrombolysis-based treatment strategies (OR 0.82, 95% CI 0.45–1.48; I² = 18%). Similarly, no statistically significant difference was observed in major complications (OR 0.68, 95% CI 0.32–1.44; I² = 42%). Mechanical thrombectomy demonstrated a tendency toward fewer minor complications (OR 0.56, 95% CI 0.30–1.03; I² = 0%). In addition, thrombectomy was associated with reduced length of hospitalization compared with catheter-directed thrombolysis (MD −3.21 days, 95% CI −5.10 to −1.32; I² = 61%). Conclusion: Mechanical thrombectomy appears to provide outcomes comparable to catheter-directed thrombolysis while offering the potential benefit of shorter hospitalization in patients with acute lower limb ischemia. These findings support thrombectomy-based therapy as a feasible endovascular treatment option in selected ALI patients.